International medical students‘ improvement in communication skills in psychosomatic care: a natural language processing based analysis [data] - Sgrott, Julia; Nikendei, Christoph; Nagy, Ede; Smirnov, Aleksei; Arias Alvarado, Josefina; Friederich, Hans-Christoph; Dönnhoff, Ivo (Universität, 2025)
In this study, we evaluated international medical students' communication skills in the context of psychosomatic medicine, after attending a three-day training seminar. Using a pre-post-assessment-design, we assessed the development in communication skills using Natural Language Processing (NLP) as well as traditional rating scales. International students significantly improved their communication style towards a more patient-centered approach. This dataverse contains the following data: all the materials used in the training seminar; the binary and global rating instruments used in the ratings; the rating results; international students' demographic data; the transcription rules in German and English, which were followed in the video transcription process; R-Markdowns with the R code used in statistical analysis of NLP parameters and rating data as well as our results. All participants were anonymized.
Gesehen am 14.01.2026
Keywords: Forschungsdaten; Datenbank